Evaluation of an Accelerated Chemoradiotherapy Protocol for Oropharyngeal Squamous Cell Carcinoma in 5 Cats and 3 Dogs. (December 2015) - Rejec, Ana; Benoit, Jerome; Tutt, Cedric; Crossley, David; Butinar, Janos; Hren, Natasa Ihan
Accelerated radiation therapy protocols address the specific biology of aggressive oropharyngeal squamous cell carcinoma and this approach was applied in 5 feline and 3 canine oropharyngeal squamous cell carcinoma patients where surgery was not possible (4/5 feline and 2/3 canine cases) or was declined (1/5 feline and 1/3 canine cases). A protocol using 14 fractions of 3.5 Gy over 9-days, combined with carboplatin chemotherapy as a radiosensitiser (total dose 180 mg/m 2 in feline and 300 mg/m 2 in canine cases) resulted in a complete tumor response in most cases (4/5 feline and 3/3 canine cases) with acceptable acute and long-term side effects. Results achieved in feline cases correspond with published data where these specific radiotherapy protocols were employed. A complete response and long-term survival (> 2-years) was achieved in all canine patients. Although no standardized chemoradiotherapy protocols currently exist, this therapeutic approach can be a useful addition for the management of oropharyngeal squamous cell carcinoma of cats and dogs when the goals of treatment include maximizing tumor control while maintaining function and quality of life.